2018
DOI: 10.1016/j.nicl.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Using simultaneous PET/MRI to compare the accuracy of diagnosing frontotemporal dementia by arterial spin labelling MRI and FDG-PET

Abstract: PurposeThe clinical utility of FDG-PET in diagnosing frontotemporal dementia (FTD) has been well demonstrated over the past decades. On the contrary, the diagnostic value of arterial spin labelling (ASL) MRI – a relatively new technique – in clinical diagnosis of FTD has yet to be confirmed. Using simultaneous PET/MRI, we evaluated the diagnostic performance of ASL in identifying pathological abnormalities in FTD (FTD) to determine whether ASL can provide similar diagnostic value as FDG-PET.MethodsASL and FDG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…bvFTD behavioral variant frontotemporal dementia, SD semantic dementia, PNFA progressive non-fluent aphasia, 3R three repeat, 4R four repeat, CBD corticobasal degeneration, PSP progressive supranuclear palsy, AGD argyrophilic grain disease, TDP TAR DNA binding protein, FTDP frontotemporal degeneration and Parkinsonism, FUS fused in sarcoma, UPS ubiquitin-proteasome system, DLDH dementia lacking distinctive histology brain perfusion images, and was verified for diagnosing FTD [45]. However, the accuracy for discriminant diagnosis of FTD patients from healthy subjects using ASL was reported to be inferior to that with FDG-PET [46], and ALS may not be widely available for use in clinical examination.…”
Section: Bvftdmentioning
confidence: 99%
“…bvFTD behavioral variant frontotemporal dementia, SD semantic dementia, PNFA progressive non-fluent aphasia, 3R three repeat, 4R four repeat, CBD corticobasal degeneration, PSP progressive supranuclear palsy, AGD argyrophilic grain disease, TDP TAR DNA binding protein, FTDP frontotemporal degeneration and Parkinsonism, FUS fused in sarcoma, UPS ubiquitin-proteasome system, DLDH dementia lacking distinctive histology brain perfusion images, and was verified for diagnosing FTD [45]. However, the accuracy for discriminant diagnosis of FTD patients from healthy subjects using ASL was reported to be inferior to that with FDG-PET [46], and ALS may not be widely available for use in clinical examination.…”
Section: Bvftdmentioning
confidence: 99%
“…Compared to FDG PET, ASL has the advantage of not requiring any injection of radiotracers or exogenous contrast agents, making its acquisition more acceptable (20). ASL studies have found evidence of hypoperfusion patterns that mirror those seen with FDG PET in Alzheimer's disease and fronto-temporal dementia (19,21,22). Conversely, patterns of ASL-derived hypoperfusion have not yet been confirmed as a valuable biomarker for the risk of developing cognitive impairment in PD.…”
Section: Introductionmentioning
confidence: 99%
“…The performance comparison between FDG-PET and arterial spin labeling (ASL) MRI diagnostic value in identifying the pathological abnormalities of frontotemporal dementia (FTD) is studied in [54]. Twenty subjects are considered to determine the qualitative and quantitative diagnostic utility of ASL and FDG-PET for analyzing the ROI and subjective visual ratings.…”
Section: B Pet Modalitiesmentioning
confidence: 99%
“…It is predicted that multi-modal molecular imaging can seizure the corresponding information of a patient in a single scan such as the recent development PET/MRI or SPECT/MRI or PET/CT or SPECT/CT which has the advantages including spatial and temporal resolution, functional anatomical basis, targeting disease biomarkers with high accuracy in brain research. Temporal and spatial registration of simultaneous PET/MRI is assessed in [105], where Arterial Spin Labeling (ASL) is shown to be an alternative of FDG-PET for clinical diagnosis of bvFTD. So based on the recent advancement of medical image modalities along with their analysis technologies in dementia diagnosis, the performance of automatic dementia diagnosis is noticeably improving.…”
Section: Major Challenges and Future Prospectsmentioning
confidence: 99%